2013
DOI: 10.1002/jmv.23652
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus infection in women in some cities and regions of Bulgaria

Abstract: This aim of this study was to evaluate the prevalence of human papillomavirus (HPV) infections among women (aged 15-55 years) in four of the biggest cities and regions in Bulgaria (viz., Sofia, Plovdiv, Varna, and Burgas), as well as in two other smaller cities (viz., Pleven and Vidin). Furthermore, study aimed to identify the prevalence of the 12 high-risk HPV (HR-HPV) genotypes in 2012, and to predict the benefits of a future national vaccination campaign for 12-year-old girls in Bulgaria. This HPV genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 7 publications
5
14
1
Order By: Relevance
“…Similar to some European studies, we found that in our region HPV18 was present at a lower percentage and its frequency was five times lower than that of HPV16 (27). Furthermore, if we consider the distribution of HVP genotypes in the Balkan countries (Table 4), it could clearly be seen that the frequency of HPV 18 ranks fourth or fifth in most countries, enabling us to label it as a regional characteristic (16,(28)(29)(30)(31)(32)(33)(34)(35). Although many studies clearly state that the presence of HPV18 increases with the severity of cytological lesions (18,21), we found it in 1.41%, 3.74%, 4.03%, and 3.63% of the NILM, ASCUS, LSIL, and HSIL groups, respectively, with no statistical significance in the differences among them.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to some European studies, we found that in our region HPV18 was present at a lower percentage and its frequency was five times lower than that of HPV16 (27). Furthermore, if we consider the distribution of HVP genotypes in the Balkan countries (Table 4), it could clearly be seen that the frequency of HPV 18 ranks fourth or fifth in most countries, enabling us to label it as a regional characteristic (16,(28)(29)(30)(31)(32)(33)(34)(35). Although many studies clearly state that the presence of HPV18 increases with the severity of cytological lesions (18,21), we found it in 1.41%, 3.74%, 4.03%, and 3.63% of the NILM, ASCUS, LSIL, and HSIL groups, respectively, with no statistical significance in the differences among them.…”
Section: Discussionsupporting
confidence: 87%
“…The International Agency for Research on Cancer has classified HPV 16 and 18 as human cervical carcinogens since 1995 (5). By 2011 the group was expanded to include HPV 31,33,35,39,45, 51, 52, 56, 58, and 59 (6). It is estimated that over 50%-80% of sexually active women will be infected with one or more genital HPV types during their lives, with a peak prevalence in young sexually active individuals (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the available data are insufficient to assess the epidemiology of HPV among women in Bulgaria . For example, the prevalence of mixed infections by region and age group is unknown, as are changes in incidence, if any, following the introduction of prophylactic vaccines against the most common genotypes in 2012. In this light, a previous study in 2012 examined the distribution and prevalence of 12 high‐risk HPV genotypes in women between 15 and 54 years of age in the four biggest cities and regions of Bulgaria (viz., Sofia, Plovdiv, Varna, and Burgas) and in two smaller communities (viz., Pleven and Vidin).…”
Section: Introductionmentioning
confidence: 99%
“…In this light, a previous study in 2012 examined the distribution and prevalence of 12 high‐risk HPV genotypes in women between 15 and 54 years of age in the four biggest cities and regions of Bulgaria (viz., Sofia, Plovdiv, Varna, and Burgas) and in two smaller communities (viz., Pleven and Vidin). This survey was also designed to predict the potential benefits of the planned national campaign that began in 2012 to immunize all 12‐year‐old girls against HPV …”
Section: Introductionmentioning
confidence: 99%